2021
DOI: 10.55563/clinexprheumatol/7ullgb
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine cardiotoxicity: a case-control study comparing patients with COVID-19 and patients with systemic lupus erythematosus

Abstract: ObjectiveAntimalarials have been associated with QT prolongation in COVID-19 patients but are generally safe in systemic lupus erythematosus (SLE).We compared the prevalence of QTc prolongation between COVID-19 and SLE patients treated with hydroxychloroquine (HCQ). Methods We included patients with SARS-CoV-2 infection confirmed by nasopharyngeal swab and patients taking HCQ for SLE.A prolonged QTc was defined as an increase in QTc intervals >60 ms (compared with baseline) or as a QTc of ≥500 ms. We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…HCQ alone led to more pronounced QTc prolongation than combinations with azithromycin, where the QTc was notably lower. [11][12][13] This could be influenced by the younger average age of our participants (51 years) compared to those in studies by Mancuso et al [14] (70.5 years) and Rosenberg et al [15] (over 60 years), suggesting a potential impact of age and baseline cardiac health on drug metabolism and the pharmacokinetics of HCQ.…”
Section: Comparative Analysis Of Treatment Regimensmentioning
confidence: 61%
“…HCQ alone led to more pronounced QTc prolongation than combinations with azithromycin, where the QTc was notably lower. [11][12][13] This could be influenced by the younger average age of our participants (51 years) compared to those in studies by Mancuso et al [14] (70.5 years) and Rosenberg et al [15] (over 60 years), suggesting a potential impact of age and baseline cardiac health on drug metabolism and the pharmacokinetics of HCQ.…”
Section: Comparative Analysis Of Treatment Regimensmentioning
confidence: 61%
“…Furthermore, concerns about risk for QT prolongation and increased rate of arrythmias which were noticed in patients with COVID-19 who were treated with antimalarials during the early phase of the pandemic finally resulted in abandonment of HCQ. Mancuso et al reported a QTc prolongation in 17% of COVID-19 patients treated with HCQ[ 99 ], a finding typically not seen in SLE patients chronically treated with the drug [ 100 , 101 ].…”
Section: Covid-19 In Patients With Slementioning
confidence: 99%
“…Furthermore, the use of antiviral drugs could also cause an increase in the QTc interval for up to 72 h after treatment, with the prolongation of the QTc interval observed in 36.3% of patients [5]. Some studies have also suggested that a combined arrhythmogenic effect of the SARS-CoV-2 infection and hydroxychloroquine could account for the excess of QTc prolongation and fatal arrhythmias previously described in some COVID-19 patients [6].…”
Section: Introductionmentioning
confidence: 99%